How Do Governments Spend Their Public Spending? - Luthfia, Munhamik; Siregar, Baldric (Jurnal Economia, 2016)
Abstract: How Do Governments Spend Their Public Spending? The objectives of this study are to examine whether the local expenditure for education, health, and economic influence economic welfare, and whether population influences the relationship between them. This study used the sample of all province in Indonesia 2008-2013, except Kalimantan Utara Province. The method used in this study is multiple regression methods. The result of this study states that education expenditure had a significant positive effect, health expenditure had not significant negative effect, while economic expenditure had a significant negative effect on the welfare. Population as the moderating variable cannot moderate the relationship between that expenditure with the welfare.Keywords: education expenditure, health expenditure, economic expenditure, population, and welfare.Abstrak: Bagaimana Pemerintah Mengalokasikan Pengeluaran Publiknya? Tujuan penelitian ini adalah untuk menguji apakah belanja daerah untuk belanja pendidikan, kesehatan, dan ekonomi mempengaruhi kesejahteraan, dan apakah populasi mempengaruhi hubungan antara ketiga belanja tersebut dengan kesejahteraan. Penelitian ini menggunakan sampel seluruh provinsi di Indonesia tahun 2008-2013, kecuali Provinsi Kalimantan Utara. Metode yang digunakan adalah metode regresi berganda. Hasil penelitian menunjukkan bahwa belanja pendidikan memiliki pengaruh positif, belanja kesehatan memiliki pengaruh negatif tidak signifikan, dan belanja ekonomi memiliki pengaruh negatif signifikan terhadap kesejahteraan. Populasi sebagai variable moderasi tidak mampu memoderasi hubungan antara ketiga belanja tersebut dengan kesejahteraan.Kunci: belanja pendidikan, belanja kesehatan, belanja ekonomi, populasi penduduk, dan kesejahteraan masyarakat.